Enhancing Chinese Character Mastery: The Role of Digital Apps in Teaching Stroke Order to Foreign Language Learners - Annisa Syauqina Kadar; Muthia Mutmainnah Darmuh; Jusriana Sartika Sumule; Winda Ayu Utami Rhamadanty (Jurusan Teknik Informatika dan Komputer, 2024)
Learning Chinese characters, a fundamental aspect of mastering the Chinese language, presents unique challenges due to its logographic nature and the critical importance of stroke order. Traditional methods of teaching stroke order, often through repetitive writing drills, can be monotonous and less engaging. This study explores the effectiveness of digital applications in teaching stroke order to Chinese-as-a-Foreign Language (CFL) learners, specifically focusing on the